Multispacecraft wave analysis of current sheet flapping motions in Earth’s magnetotail - Petrenko, Bohdan; Kozak, Liudmyla; Kronberg, Elena; Akhmetshyn, Roman (Frontiers in Astronomy and Space Sciences, 2023)
In our work, for the first time, we conducted a comprehensive multispacecraft wave study of flapping current sheet oscillations in the Earth's magnetotail. Measurements taken from the Magnetospheric Multiscale (MMS) mission were analyzed for two flapping events with different morphologies of oscillation behavior: stationary-like and kink-like type. A comparison of the results calculated by the methods of phase difference, wave surveyor and Multipoint Signal Resonator technique was carried out. For the first time using observations, it was found that the energy distribution of wavy magnetic field contains complex multi-branch dispersion dependencies on $k_y$, $k_z$. The phase velocities of propagation of flapping oscillations were estimated. The used methods complement each other, and their differences made it possible to assess the presence of nonlinear wave packets during kink flapping and the azimuthal asymmetry of the current sheet profile.